Un cadre interprétatif pour enrichir la réflexivité : le cas d’une formation à la médiation civile et commerciale - Valérie Saint‑Dizier de Almeida; Flora Ilardo; Isabelle Serre; Olivier Cachard; Guy Deloffre (Activités)
Reflection on professional practices by professionals themselves in collective discussions allows them to improve their understanding of work activities, and to develop reflexivity skills. In the educational field, one challenge is to offer new interpretive frameworks allowing professionals to perceive their activity in a new light and enhance reflection on practices in collective discussion. The goal of this paper is to present a new interpretive framework that can be used to study professional practices that take place through linguistic interactions. This framework includes models, theories, concepts and methodologies taken from language sciences and the psychology of communication. The issue in this paper is to study how this framework contributes to the process of training lawyers and notaries in civil and commercial mediation. The training system uses: (i) the role-play technique, (ii) the results of the analysis of verbal productions voiced during role-play (analysis based on the framework), (iii) a collective discussion consecutive to the role-play and (iv) a discussion in allo-confrontation, during which the results of the analysis are presented. From this study, we can see that the restitution of the results of the role play analysis based on the framework clarifies the communicational activity from viewpoints that are not immediately accessible to the trainees. It also makes it possible to revise dysfunctions/phenomena that have so far gone unnoticed. Above all, it provides conceptual tools for a reflexivity that might be useful in the optimization of professional practice.